Efecto del abono orgánico en el cultivo de ajonjoli sesamum indicum l variedad compuesto enano - Aguilar Nagua, Pablo Alexander (2011)
This research was carried out at Santa Inés experimental farm belong to the Technical University of Machala. There was investigated the effect of four organic fertilizers in the variety ‘dwarf composed’ os sesame (Sesamumindicum L.). The objectives were: 1.Determine the effects of the compost in cultivation of Sesame; 2.Selection organic fertilizer and proper doses. 3. Economic analysis of treatments. The treatments evaluated were: Biol. 3000 l /, Humus of lombriz 4000 kg / ha, Bokashi 3000 kg / ha, Compost 5000 kg/ha and a tester. The experimental design used was blocks at random with four repetitions. Evaluated variables were: days to germination, days to flowering, height of floor 30, 45, 60 and 90 days after sowing. Other variables analyzed were the number of capsules per plant, number of seeds by boilerplate and weight of 1000 seeds. During this work it was realized irrigation, thinning, pest and disease control. Statistical analysis of the results determined that organic fertilizersinfluenced in plant height. The number of capsules per plant,the best effects weregot by Humus 4000 kg/ha. We also found significant response to the weight of 1000 seeds and grain production. The best yields was reached by Humus that got 2797 kg/ha, Bokashi 2497 kg/ha and Biolwith 2322 kg/ha. The treatment Humus 4000 kg/ha, achieved greater profitability, but in terms of benefit/cost was under less than 1.0 (978/1265), that mean that for each dollar spent was 0.77 gain.